Strategy for strengthening the creative industry through the study of Jombangan Batik aesthetics and analysis of its manufacturing process - Nurcahyanti, Desy; Kholis, Achmad Nur; Hastuti, Dian Lestari; Ayob, Norhayati (Gelar: Jurnal Seni Budaya, 2025)
The strategy of developing creative industries based on local wisdom is a means that can be adapted in the era of technological development. This effort can be done by analyzing the in-depth part of cultural products such as batik. The existence of batik, which not only covers the world of art, culture but also industry, can be utilized as a basis for building strategies. Exploring the strategy of strengthening local wisdom-based creative industries is obtained through the process of studying Jombangan Batik in East Java using qualitative methods. Data collection techniques in the form of observation and interviews were conducted at CV. Chariesma Batik Sejahtera is a batik production site in Jombang Regency. Data mining is also strengthened through literature review techniques with aligned topics. It was found that the strategy of using local wisdom in CV. Chariesma Batik Sejahtera utilizes local wisdom in the pre-production stage to produce sales. This can be a foundation or model to be applied in other creative industries. The utilization of local wisdom as a source of ideas in making products, ranging from materials, naming, values, and visuals. The manufacturing process can also include local wisdom, such as the value of protecting the environment and improving work skills. Thus, this strategy can be implemented and become an inspiration for other creative industries in incorporating elements and values from local wisdom.